Kontribusi Penguasaan Unsur-Unsur Pembangun Puisi Terhadap Kemampuan Menulis Puisi Siswa Kelas VIII MtsS. Al-Wahliyah Asahan Mati Tahun Pembelajaran 2022/2023 (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
This study aims to (1) analyze the mastery of the building blocks of poetry for class VIII students of MTsS Al-Washliyah Asahan Mati, (2) analyze the ability to write poetry for class VIII students of MTsS. Al-Washliyah Asahan Mati, (3) Knowing and describing the contribution of mastery of the building blocks of poetry to the ability to write poetry for class VIII MTsS students. Al-Washliyah Asahan Dead. This study uses correlational research methods by collecting data by observation in the form of giving questions and writing poetry assignments. From the results of this study, it was found that the correlation between mastery of the building blocks of poetry on the ability to write poetry was in the high category, amounting to 0.654457. It was also found that the coefficient of determination was 42.83 or 43%. That is, mastery of the building blocks of poetry (X) influences and contributes to the ability to write poetry (Y) by 43%.